TIGA SPESIES PERONOSCLEROSPORA PENYEBAB PENYAKIT BULAI JAGUNG DI INDONESIA - Ummu S. Rustiani; Meity S. Sinaga; Sri Hendrastuti Hidayat; Suryo Wiyono (BERITA BIOLOGI, 2015)
Downy mildew is very detrimental disease of maize production in Indonesia. Adequate information regarding the identification key based on morphological and morphometric characteristic of the causal fungi of maize downy mildew in Indonesia is limited. Study for detection and identification of morphological, morphometric, and moleculer base is urgently required. Artificial sporulation induction method performed to obtain the morphology of the fungus as a whole.The fungi were morphologically identified as symptomatic maize downy mildew collected from 13 provinces in Indonesia.Three species, namely P. maydis, P.sorghi, and P. philippinensis were identified based on the shape,size, and conidial cell wall thickness, size and number of branching coniodiophores, and long sterigmata.Confirmation by PCR succesfully amplified target DNA of P. maydis, P. sorghi, and P. philippinensis. The identification key of third species of Peronosclerospora accurately to be used in identification of Peronosclerospora causes downy mildew of maize in Indonesia.This identification key is recommended as a method of identification of the causal downy mildew of maize in Indonesia.